Progress Report on Inclusion of Enhanced Contractual Provisions in International Sovereign Bond Contracts. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
As part of the Fund's ongoing work on sovereign debt restructuring, in October 2014 the Executive Board endorsed the inclusion of key features of enhanced pari passu provisions and collective action clauses (CACs) in new international sovereign bonds.1 Specifically, the Executive Board endorsed the use of: (i) a modified pari passu clause that explicitly excludes the obligation to effect ratable payments and (ii) an enhanced CAC with a menu of voting procedures, including a 'single-limb' voting procedure that enables bonds to be restructured on the basis of a single vote across all affected instruments, a two-limb aggregated voting procedure and a series-by-series voting procedure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet